2020
DOI: 10.3390/ijerph17207665
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Sedentary Behavior Research in Indonesian Youth: A Scoping Review

Abstract: Background: This study aimed to map physical activity and sedentary behaviour research trends, designs, and topics for Indonesian youth. Methods: This review conforms to the “Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR).” A systematic search on eight platforms was performed in August 2018 and was updated in April 2020. Results: From 10,753 documents screened, 166 met the selection criteria. Over half of the studies were cross-sectional, and the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 40 publications
2
13
0
1
Order By: Relevance
“…Laporan Nasional RISKESDAS, 2013 , National Institute for Health Research and Development (NIHRD), Ministry of Health, Republic of Indonesia. Laporan Nasional RISKESDAS, 2018 ), which was similar to our study, although the proportions were lower in children and adolescents (12–52%) ( Pengpid and Peltzer, 2019 , Andriyani et al, 2020 ). However, whereas we observed that alcohol consumption was low (2%), another online survey study in 4,584 participants during COVID-19 lockdown in 2020 reported that the prevalence was higher (9.5%), although it was unclear whether the higher consumption of alcohol was associated with the social restriction ( Hanafi et al, 2021 ).…”
Section: Discussionsupporting
confidence: 91%
“…Laporan Nasional RISKESDAS, 2013 , National Institute for Health Research and Development (NIHRD), Ministry of Health, Republic of Indonesia. Laporan Nasional RISKESDAS, 2018 ), which was similar to our study, although the proportions were lower in children and adolescents (12–52%) ( Pengpid and Peltzer, 2019 , Andriyani et al, 2020 ). However, whereas we observed that alcohol consumption was low (2%), another online survey study in 4,584 participants during COVID-19 lockdown in 2020 reported that the prevalence was higher (9.5%), although it was unclear whether the higher consumption of alcohol was associated with the social restriction ( Hanafi et al, 2021 ).…”
Section: Discussionsupporting
confidence: 91%
“…Qualitative research has also found that Indonesian adolescents often eat away from home and purchased food from vendors [14,15]. Moreover, lower levels of baseline physical activity are consistent with prior studies suggesting that adolescents in Indonesia are sedentary [15,20,21].…”
Section: Discussionsupporting
confidence: 76%
“…For more details, see To determine the level of sedentary subjects in the study, the percentage of low and high inactive categories between SAWd and SAWe was calculated, respectively. The passive activity level increases if the sedentary activity value is > 5 hours/day, and the low if the stagnant activity value is 5 hours/day [11]. Table 1 showed the percentage result of 95.36%, which is at a low level in SAWd, while in SAWe showed the percentage result of 79.47%.…”
Section: Resultsmentioning
confidence: 93%
“…This includes sitting at leisure, commuting to work, and at work and home [10]. High sedentary activity is characterized by a passive activity carried out > 5 hours per day [11].…”
Section: Introductionmentioning
confidence: 99%